THE URGENCE OF IMPLEMENTING LAW IN MONEY LAUNDERING ON THE ERADICATION OF CORRUPTION TO OPTIMIZE THE RECOVERY OF STATE FINANCIAL LOSS - Tambunan, Ria Berlian; Sholehuddin, Dr. M. (jfpublisher, 2022)
Corruption in Indonesia has not decreased, as reflected in the Transparency International report. Indonesia's Corruption Perception Index (CPI) dropped by 3 points, from 40 in 2018–2019 to 37 in 2019–2020. One major impact of corruption is the loss of state finances; therefore, a different approach is needed to eradicate corruption effectively. This would ensure that state financial losses can be optimally recovered and reused for the nation's benefit and the people's prosperity. The research method employs a normative approach with a legislative framework. Additionally, it utilizes secondary legal materials, particularly literature that examines the correlation between corruption and money laundering. The research concludes that money laundering and corruption are closely linked, as the original crime stems from corruption. This is clearly and explicitly stated in Article 2, Paragraph (1) of Law No. 8/2010. Furthermore, Law No. 8/2010 does not only punish active and passive perpetrators but also regulates legal actions such as asset confiscation and recovery. This is achieved through tracking assets derived from crimes at different stages: placement of illicit funds into the financial system, layering, and ultimately, asset recovery, where transacted and utilized funds are reclaimed.